The Influence of Measurement Error on Stunting Rates in Egypt - Figueroa, Jose Luis; Kurdi, Sikandra (2018)
as part of the IFPRI-Egypt Seminar Series- funded by the United States Agency for International Development (USAID) project called “Evaluating Impact and Building Capacity” (EIBC) that is implemented by IFPRI.